Calendar anomalies, global uncertainty and volatility the impact on selected Islamic stock market returns / Norashikin Adam - Adam, Norashikin (2023)
The purpose of this study is to investigate the impact of calendar anomalies, global uncertainty and volatility on selected Islamic stock market returns. Efficient Market Hypothesis states that no abnormal profit can exist in any form of efficient market. Alternatively, Adaptive Market Hypothesis suggests there is chance of abnormal profit that can be earned from existence of calendar anomalies. Given the two competing theories, this study presents an attempt to test whether calendar anomalies exist in the Islamic stock market returns. This study investigates three different types of calendar anomalies: the day of the week effect, the month effect, and the holiday effect. Besides, this study also examines the impact of global uncertainty and volatility by using Global Economic Policy Uncertainty (GEPU) and Volatility Index (VIX) as proxies across 10 Islamic stock market returns- Dow Jones Islamic Market (DJIM), Saudi Arabia, Malaysia, United Arab Emirates (UAE), Kuwait, Qatar, Turkey, Indonesia, Bahrain, Pakistan—for 20 years from 25 September 2000 to 24 September 2020. For calendar anomalies, this study used GARCH for the baseline models and EGARCH for the robustness test. For global uncertainty and volatility, this study relied on Markov Switching Model for the baseline models and Wavelet Coherence for the robustness test. The findings inferred that calendar anomalies are present in Islamic stock market returns for DJIM, Indonesia, and Pakistan (day of the week effect), all countries except Kuwait, Qatar, and Pakistan (month effect), and Indonesia, the UAE, and Qatar (holiday effect). The findings also showed that global uncertainty captured by Global Economic Policy Uncertainty had significant negative impacts on all countries except Saudi Arabia, Kuwait, and Qatar. Furthermore, volatility presented by the Volatility Index had significant impacts on all countries except Pakistan, Kuwait, the UAE, and Qatar. Overall, calendar anomalies, global uncertainty and volatility have significant impact on the Islamic stock market returns in this study. The findings can assist investors who seek to diversify their portfolios and achieve their investment goals, as well as for investors seeking to diversify their portfolios so as to maximise return and minimise risk. The results also provide information to policymakers about the current state of Islamic stock market returns.